Integrated precision medicine: the role of electronic health records in delivering personalized treatment. (16th February 2017) - Sitapati, Amy; Kim, Hyeoneui; Berkovich, Barbara; Marmor, Rebecca; Singh, Siddharth; El‐Kareh, Robert; Clay, Brian; Ohno‐Machado, Lucila
Abstract : Precision Medicine involves the delivery of a targeted, personalized treatment for a given patient. By harnessing the power of electronic health records (EHRs), we are increasingly able to practice precision medicine to improve patient outcomes. In this article, we introduce the scientific community at large to important building blocks for personalized treatment, such as terminology standards that are the foundation of the EHR and allow for exchange of health information across systems. We briefly review different types of clinical decision support (CDS) and present the current state of CDS, which is already improving the care patients receive with genetic profile‐based tailored recommendations regarding diagnostic and treatment plans. We also report on limitations of current systems, which are slowly beginning to integrate new genomic data into patient records but still present many challenges. Finally, we discuss future directions and how the EHR can evolve to increase the capacity of the healthcare system in delivering Precision Medicine at the point of care. WIREs Syst Biol Med 2017, 9:e1378. doi: 10.1002/wsbm.1378 This article is categorized under: Translational, Genomic, and Systems Medicine > Translational Medicine Abstract : Building blocks of personalized healthcare delivery.